Reduction of Turbidity, Color Intensity and COD of Jumputan Wastewater with Electrocogulation Method - Julian, Asha Aisha; Larasati, Wulan Ayum; Cundari, Lia (Jurnal Rekayasa Kimia & Lingkungan, 2023)
The purpose of this study was to determine the effectiveness of the electrocoagulation method in reducing turbidity, color concentration and COD levels on Jumputan wastewater treatment. The electrodes used are aluminum plates as anode and cathode. The variations of the research used were the speed of agitation and the system used (batch and intermittent system). The fixed variable used is a voltage of 3.5 volts, the 2 aluminium electrodes, and 250 ml volume of Jumputan wastewater. The results showed that the maximum turbidity degraded to 99.89% for the batch system at a contact time of 150 minutes with agitation speed of 150 rpm, and 99.97% for intermittent system at a contact time of 60 minutes with agitation speed of 150 rpm. The maximum percentage of color removal reached 58.90% for the batch system at a contact time of 90 minutes with a stirring speed of 50 rpm, and 54.74% for intermittent system at a contact time of 150 minutes with a stirring speed of 150 rpm. The electrocoagulation method could reduce 78.75% of the COD level for the batch system is and 80% for the intermittent system. The intermittent system slightly had more effect on the turbidity, color and COD reduction compared to batch system. Both batch and intermittent system got optimum turbidity and color removal on first 30 minutes of electrocoagulation process. The results prove that electrocoagulation method has been effective as an alternative to reduce COD and turbidity on Jumputan wastewater.